Ultraviolet photodegradation facilitates microbial litter decomposition in a Mediterranean climate. Issue 7 (1st July 2015) - Baker, Nameer R.; Allison, Steven D.
Abstract : Rates of litter decomposition in dryland ecosystems are consistently underestimated by decomposition models driven by temperature, moisture, and litter chemistry. The most common explanation for this pattern is that ultraviolet radiation (UV) increases decomposition through photodegradation of the litter lignin fraction. Alternatively, UV could increase decomposition through effects on microbial activity. To assess the mechanisms underlying UV photodegradation in a semiarid climate, we exposed high‐ and low‐lignin litter to ambient and blocked UV over 15 months in a Mediterranean ecosystem. We hypothesized that UV would increase litter mass loss, that UV would preferentially increase mass loss of the lignin fraction, and that UV would have a negative effect on microbial activity. Consistent with our first hypothesis, we found that UV‐blocking reduced litter mass loss from 16% to 1% in high‐lignin litter and from 29% to 17% in low‐lignin litter. Contrary to our second hypothesis, UV treatment did not have a significant effect on lignin content in either litter type. Instead, UV‐blocking significantly reduced cellulose and hemicellulose mass loss in both litter types. Contrary to our third hypothesis, we observed a positive effect of UV on both fungal abundance and the potential activities of several assayed extracellular enzymes. Additionally, under ambient UV only, we found significant correlations between potential activities of cellulase and oxidase enzymes and both the concentrations and degradation rates of their target compounds. Our results indicate that UV is a significant driver of litter mass loss in Mediterranean ecosystems, but not solely because UV directly degrades carbon compounds such as lignin. Rather, UV facilitates microbial degradation of litter compounds, such as cellulose and hemicellulose. Thus, unexpectedly high rates of litter decomposition previously attributed directly to UV in dryland ecosystems may actually derive from a synergistic interaction between UV and microbes.